MAKNA FILOSOFI YOGA BALI KUNO DAN IMPLEMENTASINYA SEBAGAI TUJUAN WISATA - D.E., Relin; Sena, I Gusti Made Widya; Perni, Ni Nyoman; Wedanti, I Gusti Ayu Jatiana Manik (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
This research aims to analyze the concept of ancient Balinese yoga philosophy and to revitalize it as a tourism destination. Through this research, it is hoped that practitioners, universities, and society can consider ancient Balinese yoga as an alternative tourism destination in Bali. This research uses a qualitative research method. The data collection method includes observation, interviews, documentation, and literature review. The analysis techniques used are data reduction, data presentation, and data verification. The theories supporting this research are communication semiotics theory and practice theory. The findings of this research are threefold: 1) the historical and static development of ancient Balinese yoga, 2) the philosophy of yoga in the Windu Sara Foundation consisting of various philosophical knowledge, and 3) the revitalization of ancient Balinese yoga as an alternative tourism destination can be applied as a form of religious tourism.